1970
DOI: 10.1128/jb.104.2.834-838.1970
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Preliminary Characterization of Developmental Mutants from Microsporum gypseum

Abstract: Developmental mutants affected in either sporulation or spore germination have been isolated from Microsporum gypseum with the aid of nitrosoguanidine or as spontaneously occurring mutants. The time course levels of several proteins temporally associated with conidial development have been assayed in the wild-type and mutant strains. The spore germination characteristics of two of the mutants are described. The relationship of alkaline protease accumulation to tyrosinase accumulation and spore germination is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1971
1971
1982
1982

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The chymotrypsin-like preference of the germination protease for aromatic amino acids has been reported previously (14,15). The resistance of the beta-keratin is thought to be due to cross-linking between tyrosine residues; thus, treatments which are active against tyrosine would solubilize the beta-keratin fraction (1).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The chymotrypsin-like preference of the germination protease for aromatic amino acids has been reported previously (14,15). The resistance of the beta-keratin is thought to be due to cross-linking between tyrosine residues; thus, treatments which are active against tyrosine would solubilize the beta-keratin fraction (1).…”
Section: Discussionmentioning
confidence: 95%
“…Organisms and growth conditions. The growth and sporulation characteristics of the strain of M. gypseum, designated R87, used in these studies have been described elsewhere (15,22). A mutant strain B17 of the wild-type strain also was used (15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The waterinsoluble glycoprotein from spores was notably low in basic amino acids and had an increased content of acidic amino acids. The water-insoluble glycoprotein also contained considerable quantities of aromatic amino acids, which could make this fraction susceptible to alkaline germination protease attack in vivo (12). The amino acid analysis of the glycoprotein fractions revealed that the ethylenediaminesoluble, water-soluble glycoproteins from both strain R87 spores and R87P1 vegetative hyphae were of similar composition, suggesting that, if the water-soluble glycoprotein of the spores was derived from its mycelial counterpart, it had undergone very little compositional transformation during sporulation.…”
Section: Discussionmentioning
confidence: 99%
“…A strain of M. gypseum (Bodin; Guiart and Grigorakis, 1928; designated strain R87) originally obtained from F. Blank, Temple University, Philadelphia, Pa., was used in these investigations. This strain was previously designated SP+Pig+ (8). An asporogenous pleomorphic strain of R87, previously designated SP2 Pig- (8), also was used in these studies.…”
Section: Methodsmentioning
confidence: 99%